Goals and Principles of Providers Working with People Experiencing Homelessness: A Comparison Between Housing First and Traditional Staircase Services in Eight European Countries - Marta Gaboardi (International Journal of Environmental Research and Public Health, 2019)
The implementation and adaptation of the Housing First (HF) model represented profound changes the structure and delivery, goals, and principles of homeless services. These features of homeless services directly influence providers, their work performance and the clients’ outcomes. The present research, conducted in eight European countries, investigated how social providers working in HF or TS (Traditional Staircase) describe and conceptualize the goals and the principles of their services. Data were collected through 29 focus group discussions involving 121 providers. The results showed that HF and TS had similar and different goals for their clients in the following areas: support, social integration, satisfaction of needs, housing, and well-being. HF providers emphasized clients’ autonomy and ability to determine their personal goals, with housing being considered a start on the path of recovery, while TS were more focused on individual clients’ basic needs with respect to food, health and finding temporary accommodations. HF providers privileged the person-centered approach and housing as a right, while TS providers were more focused on helping everyone. Implications of the results are discussed as suggestions both for practice and for research.